How Can Odors Be Measured? An Overview of Methods and Their Applications - Carmen Bax (Atmosphere, 2020)
In recent years, citizens’ attention towards air quality and pollution has increased significantly, and nowadays, odor pollution related to different industrial activities is recognized as a well-known environmental issue. For this reason, odors are subjected to control and regulation in many countries, and specific methods for odor measurement have been developed and standardized over the years. This paper, conceived within the H2020 D-NOSES project, summarizes odor measurement techniques, highlighting their applicability, advantages, and limits, with the aim of providing experienced as well as non-experienced users a useful tool that can be consulted in the management of specific odor problems for evaluating and identifying the most suitable approach. The paper also presents relevant examples of the application of the different methods discussed, thereby mainly referring to scientific articles published over the last 10 years.